2016
DOI: 10.1111/jcmm.13022
|View full text |Cite
|
Sign up to set email alerts
|

A novel P53/POMC/Gαs/SASH1 autoregulatory feedback loop activates mutated SASH1 to cause pathologic hyperpigmentation

Abstract: Abstractp53‐Transcriptional‐regulated proteins interact with a large number of other signal transduction pathways in the cell, and a number of positive and negative autoregulatory feedback loops act upon the p53 response. P53 directly controls the POMC/α‐MSH productions induced by ultraviolet (UV) and is associated with UV‐independent pathological pigmentation. When identifying the causative gene of dyschromatosis universalis hereditaria (DUH), we found three mutations encoding amino acid substitutions in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Because the ERK1/2 signalling pathway is identified to be responsive to p53‐POMC‐SASH1 cascade, and the ERK1/2 signalling pathway mediates melanogenesis , we sought to address whether mutated SASH1s are induced by p53 and mutations in SASH1 promote biosynthesis of melanogenesis‐specific molecules. Our previous study showed that SASH1 mutations promote the expression of exogenous p53 and more endogenous p53 was induced by Y551D‐SASH1 mutation. Hence, we intend to identify whether p53 could promote mutated SASH1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Because the ERK1/2 signalling pathway is identified to be responsive to p53‐POMC‐SASH1 cascade, and the ERK1/2 signalling pathway mediates melanogenesis , we sought to address whether mutated SASH1s are induced by p53 and mutations in SASH1 promote biosynthesis of melanogenesis‐specific molecules. Our previous study showed that SASH1 mutations promote the expression of exogenous p53 and more endogenous p53 was induced by Y551D‐SASH1 mutation. Hence, we intend to identify whether p53 could promote mutated SASH1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Dominant SASH1 mutations are associated with dyschromatosis universalis hereditaria or multiple lentigines phenotypes, characterized by generalized mottled pigmentation and generalized lentiginosis, respectively. [144][145][146][147] Of note, SASH1 has been also identified as a tumour suppressor gene involved in the development of several solid cancers with somatic mutations. [148][149][150]…”
Section: Hyperkeratosis-hyperpigmentation Syndromementioning
confidence: 99%
“…Finally, immunoprecipitates were washed for three times with PBS and subjected to western blotting. GFP-Tag mouse Ab, Flag-tag mouse mAb, DYKDDDDK-Flag mouse mAb, GAPDH mouse mAb and anti-β-tubulin mouse mAb (Shanghai Abmart, Inc.), anti-Gαs rabbit polyclonal Ab (Gene Tex, Inc.), myc-tag mAb and HA-tag mouse mAb (Shanghai Genomics), SASH1 Rabbit mAb (Bethyl Laboratories, Inc.), TYRP1 (TA99) mouse mAb and melanoma gp100 Rabbit mAb (Abcam), Rab 27a mouse mAb (Abnova) were used for immunoblotting assay as previously described [17,18].…”
Section: Immunoprecipitation and Westernblottingmentioning
confidence: 99%
“…The melanin staining of paraffin sections obtained from epithelial tissues were performed as our previous descriptions and observed under a light microscope [18].…”
Section: Melanin Stainingmentioning
confidence: 99%
See 1 more Smart Citation